Efficacy and safety of icosapent ethyl in hypertriglyceridaemia: a recap - Parhofer, Klaus G (Eur Heart J Suppl, 2020)
Although low-density lipoprotein cholesterol lowering is effective in atherosclerotic cardiovascular disease (ASCVD) prevention, considerable ‘lipid-associated’ residual risk remains, particularly in patients with mild-to-moderate hypertriglyceridaemia (2–10 mmol/L; 176–880 mg/dL). Triglyceride (TG)-rich lipoproteins carry both TGs and cholesterol (remnant-cholesterol). At TG levels >5 mmol/L (440 mg/dL) vs. <1 mmol/L (88 mg/dL) or remnant-cholesterol >2.3 mmol/L (89 mg/dL) vs. <0.5 mmol/L (19 mg/dL), risk is ∼1.5-fold elevated for aortic stenosis, 2-fold for all-cause mortality, 3-fold for ischaemic stroke, 5-fold for myocardial infarction (MI), and 10-fold for acute pancreatitis. Furthermore, Mendelian randomization studies indicate that elevated TG-rich lipoproteins are causally related to increased risk of ASCVD and even all-cause mortality. While genetic and epidemiological data strongly indicate that TG-rich lipoproteins are causally linked to ASCVD, intervention data are ambiguous. Fibrates, niacin and low-dose omega-3 fatty acids have all been used in outcome trials, but have failed to demonstrate clear benefit in combination with statins. Whether the lack of additional benefit relates to methodological issues or true failure is indeterminate. Importantly, a recent intervention trial evaluating a high dose of eicosapentaenoic-acid showed clear benefit. Thus, REDUCE-IT evaluated the effect of icosapent ethyl (4 g/day) on cardiovascular outcomes in 8179 high-risk patients with moderate TG elevation on statin therapy. Over a median duration of 4.9 years, the relative risk for the primary endpoint (composite of cardiovascular death, non-fatal MI, non-fatal stroke, coronary revascularization, or unstable angina) was reduced by 25% (absolute risk 17.2% vs. 22.0%; P < 0.0001; number needed to treat 21). High-dose icosapent ethyl intervention therefore confers substantial cardiovascular benefit in high-risk patients with moderate hypertriglyceridaemia on statin therapy.